Risk taking for oneself and others: A structural model approach - Ferdinand M. Vieider; Clara Villegas-Palacio; Peter Martinsson; Milagros Mejía (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2015)
We examine situations in which a decision maker decides for another person as well as herself under conditions of payoff equality, and compare such decisions under responsibility to individual decisions. Estimating a structural model we find that responsibility leaves utility curvature unaffected, but accentuates the subjective distortion of very small and very large probabilities for both gains and losses. This results in an accentuation of prospect theory's four-fold pattern of risk preferences under responsibility. In addition, we also find that responsibility reduces loss aversion according to some common definitions of the latter. These results serve to reconcile some of the still largely contradictory findings in the literature on decisions for oneself and others under payoff equality.
Keywords: C93; D03; D80; O12; 330; risk preferences; responsibility; social preferences